In vitro plant regeneration of Passiflora setacea D.C. (Passifloraceae): the influence of explant type, growth regulators, and incubation conditions - Vieira, Lorena Melo; Rocha, Diego Ismael; Taquetti, Mariana Futia; Silva, Luzimar Campos da; Campos, José Marcello Salabert de; Viccini, Lyderson Faccio; Otoni, Wagner Campos (In Vitro Cellular & Developmental Biology - Plant, 2014)
The present study aimed to establish a protocol for in vitro organogenesis of Passiflora setacea and to determine the genetic stability of regenerated plants. Three types of explants (leaf, hypocotyl, and root), four growth regulator combinations [Murashige and Skoog (MS) salts, MS + 6-benzyladenine (BA), MS + thidiazuron (TDZ), and MS + BA + TDZ], and two light regimes (16-h photoperiod and continuous darkness) were tested. After 30 d on induction medium, the percentage of explants forming shoots was evaluated. Direct and indirect organogenesis was evident from hypocotyl- and root-derived explants, whereas only indirect organogenesis was observed from leaf explants. The presence of BA was essential for shoot formation from leaf explants and improved the response of hypocotyl segments under a 16-h photoperiod compared to the cytokinin-free control. However, after transfer to shoot elongation medium, the greatest number of elongated shoots was obtained from hypocotyl segments that had been induced on BA + TDZ medium under a 16-h photoperiod, as was also observed for root explants. Flow cytometry analysis confirmed the genetic stability of the regenerants based on DNA quantity (2C = 2.57 pg) in comparison with seed-derived plantlets (2C = 2.60 pg). This is the first report on the in vitro regeneration of P. setacea.
Keywords: Adventitious bud; Cytokinins; Micropropagation; Passion fruit; Shoot organogenesis; Tissue culture